TDZ Induced Organogenesis and Phytochemical Profiling of In Vitro Raised Plants of Sarpgandha (Rauvolfia serpentina L.)- An Endangered Medicinal Plant - Dhiman, Karuna; Sharma , Shipra; Soni, Priyankal; Kumari, Reena (International Journal of Economic Plants, 2025)
This study was conducted during June, 2020–2021 at Department of Biotechnology, COHF, Dr YS Parmar UHF, Neri, Hamirpur, Himachal Pradesh, India for evaluating effect of TDZ on in vitro regeneration of Rauwolfia serpentina and further phytochemicals screening of regenerants was done. Shoot tips, and leaves explants was collected from field maintained healthy plants of Rauvolfia serpentina and cultured on MS medium containing TDZ in combination with auxins. MS medium containing 1.0 mg l-1 TDZ with 0.2 mg l-1 NAA showed maximum shoot regeneration i.e. 75.3% from shoot tips within 32 days and 85.0% shoot regeneration from leaf explants. Shoots were transferred on half strength MS medium containing different auxin concentrations for in vitro rooting and maximum root regeneration percentage (89.00%) was achieved on 0.5 mg l-1 NAA. Healthy plantlets were acclimatized further on coco-peat first and then on mixture of 1:1 of sand: FYM. Donor plants as well as in vitro raised plants (six month old) were analyzed for different phytochemicals qualitatively and quantitatively. Alkaloids, flavonoids, phytosterols, tannins and phenol compound were present in leaves and roots of mother plant as well as in vitro raised plants whereas gums and mucilage was seen in mother plant but absent in in vitro raised plants. Also alkaloid, flavonoids, tannin and phenol content of in vitro raised plant were comparable higher than donor plant. Presence of important alkaloid reserpine in tissue culture raised plant was also confirmed by thin layer chromatography and Rf value of reserpine was found to be 0.92.